Outcome of single agent generic gemcitabine in platinum-resistant ovarian cancer, fallopian tube cancer and primary peritoneal adenocarcinoma. - Suprasert P. (2014)
Single original gemcitabine is commonly used as salvage treatment in platinum-resistant ovarian cancer, fallopian tube cancer and primary peritoneal adenocarcinoma (PPA) with a satisfactory outcome. However, efficacy data fro this regimen are limited. We therefore conducted a retrospective study to evaluate the outcome of patients who received single-agent generic gemcitabine (GEMITA) after development of clinical platinum resistance. The study period was between May 2008 and December 2010. Gemcitabine was administered intravenously in two different schedules: 1,000 mg/m2 on day 1,8, and 15 every 28 days; and on days 1 and 8 every 21 days with the same dosage. Administration was until disease progression was noted. The response rate was evaluated using the Gynecologic Cancer Intergroup (GCIG ) criteria while toxicity was evaluated according to WHO criteria. Sixty-six patients met the inclusion criteria in the study period. Two-thirds of them received gemcitabine as the second and third line regimen. The overall response rate was 12.1%. The median progression free survival and overall survival was 2 and 10 months, respectively. With the total 550 courses of chemotherapy, the patients developed grades 3 and 4 hematologic toxicity as follows: anemia, 1.5%; leukopenia, 13.7%; neutropenia, 27.3%; and thrombocytopenia, 3.0%. In conclusion, single agent generic gemcitabine revealed a modest efficacy in patients with platinum-resistant ovarian cancer, fallopian tube cancer and PPA without serious toxicity.